2014
DOI: 10.1515/helia-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Approach to Verticillium dahliae Infecting Sunflower

Abstract: Verticillium leaf mottle and wilt caused by the fungus Verticillium dahliae is a major disease of sunflower in Argentina and the USA. In the summer of 2013, an important outbreak of the disease occurred in one field in the Southwest of Spain. The determination of vegetative compatibility groups (VCGs) of V. dahliae is used in the genetic characterization of the fungus. Molecular markers have also been developed and applied for the analysis of V. dahliae, particularly for those isolates infecting artichoke, cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The molecular characterization of all the isolates was performed using diagnostic primers of race 1 ( Usami et al, 2007 ; de Jonge et al, 2012 ) and race 2 ( Short et al, 2014 ), as well as with the diagnostic markers of D and ND pathotypes described for Vd infecting olive tree and artichoke ( Carder et al, 1994 ; Mercado-Blanco et al, 2001 , 2002 , 2003 ; Collado-Romero et al, 2009 ). Isolates of the D pathotype of Vd are pathogenic on sunflower among other crop species ( Jiménez-Díaz et al, 2017 ), but previous findings by our research group showed that those affecting sunflower are molecularly similar to ND isolates of the fungus that are pathogenic to artichoke or cotton ( García-Carneros et al, 2014 ). Besides, races of Vd from sunflower have been determined on the basis of the reaction of particular host genotypes (or differentials) carrying genes of resistance from different sources, but racial characterization by means of molecular markers for race has not been addressed so far.…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations
“…The molecular characterization of all the isolates was performed using diagnostic primers of race 1 ( Usami et al, 2007 ; de Jonge et al, 2012 ) and race 2 ( Short et al, 2014 ), as well as with the diagnostic markers of D and ND pathotypes described for Vd infecting olive tree and artichoke ( Carder et al, 1994 ; Mercado-Blanco et al, 2001 , 2002 , 2003 ; Collado-Romero et al, 2009 ). Isolates of the D pathotype of Vd are pathogenic on sunflower among other crop species ( Jiménez-Díaz et al, 2017 ), but previous findings by our research group showed that those affecting sunflower are molecularly similar to ND isolates of the fungus that are pathogenic to artichoke or cotton ( García-Carneros et al, 2014 ). Besides, races of Vd from sunflower have been determined on the basis of the reaction of particular host genotypes (or differentials) carrying genes of resistance from different sources, but racial characterization by means of molecular markers for race has not been addressed so far.…”
Section: Methodsmentioning
confidence: 75%
“…The VCG of 38 monoconidial isolates, including those previously characterized by our research group ( García-Carneros et al, 2014 ), were determined by generation and characterization of nitrate non-utilizing ( nit ) mutants of each of them and determination of vegetative compatibility. Nit mutants were generated on Water Agar Chlorate medium as colonies presenting a faint growth on Czapek-Dox Agar (CDA) with no aerial mycelium ( Korolev and Katan, 1997 ) and phenotyped on CDA amended with hypoxanthine as described by Correll et al (1987) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All V . dahliae isolates used were previously characterized in a multidisciplinary study (Martin‐Sanz et al ., 2018b) and were selected on the basis of their different geographical origin and pathogenic race (Garcia‐Carneros et al ., 2014; Martin‐Sanz et al ., 2018b). C. helianthi isolates were selected from the plant pathogen culture collection in the Field Crop Disease Laboratory at the Institute for Sustainable Agriculture from CSIC (IAS‐CSIC) in Cordoba, Spain (Molinero‐Ruiz, 2019).…”
Section: Methodsmentioning
confidence: 99%